Instructions for gestation course: repercussions in parents who live deeply the first gestation cycle - Cordeiro Santos, Márcia Regina; Zellerkraut, Hanny; Ruela de Oliveira, Laércio (O Mundo da Saúde, 2008)
It is known that pregnancy causes several physical and emotional changes. In this period, many couples look for information in courses that instruct about gestation that purports to lighten anxiety and fears, to explain normal expectations in this phase, besides sharing experiences with people who live deeply the same situation. This study aimed to identify the expectations of parents in first gestation and childbirth, besides describing the repercussions provoked by the course in the population-target. This is a field research, exploratory, descriptive, and of quantitative nature, developed with people who attended the said Gestation course, offered by a private hospital, in the city of São Paulo. The study it counted on the participation of 30 couples and two single mothers-to-be who lived deeply their first gestation. We verify among other things that participants wanted the course to offer them knowledge and solve doubts mainly regarding childbirth, cares with pregnant women and the newborn. We conclude that the course had positive repercussions in the studied population, for more than 50% of subjects had their doubts solved, were more secure and calm after the course as to the moment they were living deeply. Some doubts had remained regarding newborns crying, choice of pediatric doctor and the ones they believed to solve or to appear after childbirth. Due to this, we believe that it is vital for public and private health institutions to invest in Education in Health.